CORRELATION OF GLOBAL REGISTRY OF ACUTE CORONARY EVENTS (GRACE) WITH THE ANGIOGRAPHIC SEVERITY AND EXTENT OF CORONARY ARTERY DISEASE IN PATIENTS WITH NON- ST ELEVATION ACUTE CORONARY SYNDROME - Khan, Zahoor Aslam; Khan, Muhammad Qaiser; Majeed, Syed Mohammad Imran (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine whether the GRACE risk score correlates with the angiographic extent and severity of coronary artery disease in patients with NSTE-ACS undergoing cardiac catheterization. Methodology: We conducted a cross sectional descriptive study in 154 patients with NSTE-ACS admitted at AFIC-NIHD from 1st April to 30th September 2011. For each patient the GRACE risk score was calculated by using specific variables collected at admission. The extent and severity of coronary artery disease was evaluated on angiography for each patient. Results: A total of 154 patients were included in the study. The average age of the patients was 55.81years. Majority (75%) of the patients was male and 25% were females. The mean GRACE score was 132.85. Overall 40 patients had low, 54 had intermediate, and 60 had high GRACE risk score. Among patients with low score 28 had SVCAD, 4 patients had DVCAD and none of the patients had TVCAD. In the intermediate group 24 patients had SVCAD, 18 had DVCAD and 6 had TVCAD whereas among the high GRACE risk score 4 patients had SVCAD, 24 had DVCAD and 32 had TVCAD. Regarding the severity of coronary artery disease; among the low GRACE risk score patients; 8 had subcritical and 32 had critical CAD. In the intermediate GRACE risk score subset of patients, 6 had subcritical and 48 had critical CAD and none of the patients of high GRACE risk score had subcritical CAD and all 60 patients had critical CAD. Conclusion: GRACE risk score is a valuable noninvasive tool in predicting the extent and severity of CAD.